Professionele vertalers as woordeboekgebruikers - Crafford, M.F.; Feinauer, Ilse (Lexikos, 2007)
Abstract: Professional translators as dictionary users. An examination of the characteristics and procedures of professional translators and the characteristics of the translation process indicate that professional translators have specific lexicographic needs that traditional bilingual dictionaries do not completely satisfy. Problems or needs that may arise during the professional translation of T2 > T1 texts and may be solved or satisfied by lexicographic data in a translation dictionary are examined. The concepts bilingual dictionary, translating dictionary and translation dictionary are discussed. On the basis of the real purpose and functions of a translation dictionary, considerations that are singled out need to be considered in the production of a translation dictionary. Keywords: TRANSLATION PROCESS, TRANSLATION COMPETENCE, TRANSLATION SKILLS, TRANSLATION DICTIONARY, BILINGUAL LEXICOGRAPHY, BILINGUALISM, TRANSLATION EQUIVALENTS, LEXICOGRAPHIC FUNCTIONS, TEXT PRODUCTION, TEXT RECEPTION Opsomming: ’n Ondersoek na die eienskappe en werkswyse van professionele vertalers en die kenmerke van die vertaalproses toon dat professionele vertalers spesifieke leksikografiese behoeftes het wat nie volledig deur tradisionele tweetalige woordeboeke bevredig kan word nie. Die probleme of behoeftes wat by die professionele vertaling van T2 > T1-tekste kan ontstaan en deur die leksikografiese data in ’n vertaalwoordeboek opgelos of bevredig kan word, word onder-soek. Die begrippe tweetalige woordeboek, vertalende woordeboek en vertaalwoordeboek word bespreek. Op grond van die werklike doel en funksies van ’n vertaalwoordeboek word oorwegings uitgelig wat by die produksie van ’n vertaalwoordeboek in ag geneem moet word. Sleutelwoorde: VERTAALPROSES, VERTAALVERMOÃ‹, VERTAALWOORDEBOEK, TWEETALIGHEID, TWEETALIGE LEKSIKOGRAFIE, VERTAALEKWIVALENTE, VERTALEN-DE WOORDEBOEK, WOORDEBOEKFUNKSIES, TEKSPRODUKSIE, TEKSRESEPSIE